Pengemasan Produk Olahan Ikan Julung-julung (Hemiramphus sp) untuk Peningkatan Ekonomi Kelompok Nelayan di Kampung Palareng - Costantein Imanuel Sarapil; Eunike Irene Kumaseh; Ganjar Ndaru Ikhtiagung (Madani : Indonesian Journal of Civil Society, 2022)
The smoked halfbeak or better known as Roa fish is the raw material for making Sambal Roa, namely souvenirs typical of North Sulawesi. Palareng Village, South Central Tabukan Subdistrict, Sangihe Islands Regency is one of the villages that produce the halfbeak. The Partner Group is an economically productive partner group, which has a business in catching, processing, and selling Roa fish. The selling price of halfbeak sold raw is on average, Rp. 1000, - / 4 tails, meaning Rp. 250, - / head. The selling price of smoked halfbeak or Roa fish is Rp. 750, - / head. Meanwhile, the price of packaged halfbeak is usually Rp. 1000, - / fish. Partner problems in developing their business are the production aspect where there are limited tools for packaging, the marketing aspect in that there is no wider marketing step, and the management aspect where there is no product management team in the partner group. The purpose of this PKM activity is to empower fishery resources, especially halfbeak (Hemiramphus sp), empower fishermen's groups in Palareng Village, produce fishery processing product permits (P-IRT: Home Industry Products) by the Sangihe Islands District Health Office, and increase the economic income of fishing groups in Palareng Village. The methods of implementing PKM are surveys, fish processing counselling, packaging of processed products, P-IRT (Home Industry Products) management and marketing management. Procurement of packaging facilities in the form of a vacuum sealer, helps the community in Palareng Village, especially the halfbeak processing group in marketing processed fish products that are more effective and efficient and increase income. The amount of partner income in selling packaged halfbeaks can reach IDR 1,000,000 - IDR 2,000,000 per trip. Increase in fishermen's income by 25%.